People's perception of the socio-cultural and environmental impacts of tourism in Malaysia: A community-reflective study - Karim, A.H.M Zehadul; Rokis, Rohaiza; Awang, Yahya (Society for Science and Education, United Kingdom, 2017)
Tourism is considered as the largest service-oriented industry of Malaysia, contributing enormously in economic terms to the GDP (gross domestic product) of the country, delivering employment to a sizeable section of the population, and fostering civic pride, social prestige, and international recognition as a desirable tourist destination. The tourism industry parades the beauty of Malaysian culture abroad as well as it enables people from outside to acquaint with a unique Muslim heritage amidst Malay modernity. Notwithstanding its many blessings, the tourism issue has sparked debate recently necessitating a discourse on a ‘rational framework for Malaysian tourism’ upon the premise that the benefits of tourism should not only be calculated in economic metrics, rather its demerits should be factored in as well. Under this circumstance, this paper empirically reflects the Malaysian community’s perception on the socio-cultural and environmental effects of tourism at the grassroots level.